Composer's video for his own work: time parallels, dotted lines, perpendiculars - Stronko, Boryslav (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the study is related to the problem of composers' self-illustrations in the YouTube presentations. The novelty of this topic is conditioned by new practice to illustrate music in YouTube. Graphic representation of music leads to the problem of correspondence between music and video. We selected only two Ukrainian composers to compare: Yuri Ishchenko and Sviatoslav Luniov. The main objective of the study is the determination of main principles of similarity or dissimilarity of time structures in music and images. The methodology is based on methods of comparison and analogy in the context of phenomenological approach to the Event in the Being Time (by late Heidegger). How the study was done: time structures of selected compositions were compared, through analogies, with the illustrating graphic events as phenomena of existential time. Thereby a number of similarities and dissimilarities were detected. Composer Y. Ishchenko preferred to illustrate his music by static images. Such a situation is a paradoxical because of the dynamic essence of his music. It establishes the problem of co-existent two time situations: in the first of them there is an integral and quasi-timeless image of music; but in the other situation there is a running stream of music structures. This approach becomes very and very fruitful because Music is able to use both the continuity, integrity of musical image as well as fluid sound events. The Y. Ishchenko's "Watercolors" for violin and piano are illustrated by several images; this approach makes it possible to mark different parts of total design (i.e. different movements or stages). Another solution one can hear and see in his "Small partita" for violin and harp. I helped him to accompany this design with fragments of animation about baroque époque. There are several GIFs - the periodically repeating images, which creates a cross-rhythm constellation with music. The significant crossfade is present in the video by Ishchenko's 3rd Violin sonata: ruined house through cross-like gap transforms in an abandoned church. The final fade of it lasts a minute. Thus, the minimal graphic processes are extremely expressive. S. Luniov mastered advanced skills in electronic music and its visual presentation. In his video "POST” he combines fragments of his own Panta Rhei for orchestra with sounds of the war. The intensity of the music development is essentially higher than that of graphic illustration, but at the end of the project the situation is opposite. In the video accompanying his Panta Rhei for orchestra S. Luniov synchronized main events and stages of the sound score with more intensive changes of the video stream and its thematic. Findings and conclusions. For the composer Y. Ishchenko, the graphic self-illustration on YouTube was mostly the outer necessity. He often limited his projects with static images for the total score or its main parts. Thus, he reinforced the integrity pole of events with the graphic ingredient of YouTube projects. Thereby, the dramaturgic tense of his compositions is concentrated in music. Such an approach was called time perpendicular strategy or time dotted line strategy. For the composer S. Luniov, the graphic self-illustration on YouTube is mostly the parallel stream of events. However, the tempo and intensity of visual and sound streams can be unequal. Such an approach is called time parallel strategy. Significance of the study follows from its conclusions, leading to more skillful and exact solutions within composers' self-illustration, i.e. in clarifying the semantic and structure design in music.